PENGARUH KOMPOSISI FILLER TERHADAP NILAI MODULUS ELASTIS MATERIAL KOMPOSIT BERPENGUAT CANGKANG KERANG DAN SERAT PINANG - Aksar, Prinob (Dinamika : Jurnal Ilmiah Teknik Mesin, 2023)
The aim of this research is to analyze the influence of filler composition on the elastic modulus of composite materials reinforced with seashell powder and betel nut fibers. The study employs a manual mixing method with varying proportions of seashell powder and betel nut fibers. Following the mixing process, samples are subjected to a tensile test to measure their elastic modulus. The research results indicate varying elastic modulus values for the composite materials. The highest elastic modulus value is achieved in the composition of 70% seashell powder, 20% betel nut fibers, and 10% resin, measuring 0.836 GPa. Meanwhile, the lowest elastic modulus value is obtained in the composition of 70% seashell powder, 10% betel nut fibers, and 20% resin, measuring 0.465 GPa. This variation is influenced by the fact that betel nut fibers generally possess greater mechanical stiffness than the matrix and seashell powder. The stiffness of these fibers significantly enhances the elastic modulus of the composite material. When these stiff fibers are embedded in a less rigid matrix, their stiffness is transferred to the composite. The quality of adhesion also plays a crucial role in ensuring effective load transfer from the matrix to the fibers, which in turn enhances the composite's stiffness and elastic modulus. The quantity and distribution of fibers in the matrix (polyester resin) and seashell powder also affect the elastic modulus. The more fibers present in the composite, the higher the elastic modulus.